2009
DOI: 10.1144/1354-079309-842
|View full text |Cite
|
Sign up to set email alerts
|

Flood basalt facies from borehole data: implications for prospectivity and volcanology in volcanic rifted margins

Abstract: Flood basalt successions cover many potentially prospective sedimentary basins world-wide, and a few instances exist of intra-basalt petroleum discoveries. However, little is known about the architecture and rock properties of the lava flows, intrusions and other lithologies that make up these successions. We present a simple, effective method of obtaining information from borehole data on the different volcanic facies within a flood basalt succession. Our aims are: (1) to provide a means of determining propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 38 publications
(51 reference statements)
4
74
0
Order By: Relevance
“…Typical signatures in logs consist of low gamma ray signatures, bulk density and neutron porosity. This is consistent with log signatures for extrusive lava flows, in contrast to intrusives which would show high bulk density (Nelson et al 2009). Due to weathering they are quite prone to washout, visible on caliper logs and generally have a high photoelectric (PEF) log response, although this is quite sensitive to washout and mudcakes (Figure 3).…”
Section: Seismic Interpretation Of Kipper Volcanicssupporting
confidence: 84%
“…Typical signatures in logs consist of low gamma ray signatures, bulk density and neutron porosity. This is consistent with log signatures for extrusive lava flows, in contrast to intrusives which would show high bulk density (Nelson et al 2009). Due to weathering they are quite prone to washout, visible on caliper logs and generally have a high photoelectric (PEF) log response, although this is quite sensitive to washout and mudcakes (Figure 3).…”
Section: Seismic Interpretation Of Kipper Volcanicssupporting
confidence: 84%
“…Several studies have shown that the physical volcanology of a flood basalt sequence (including the lava flow facies) can be derived from wireline log data using characteristic velocity and density profiles (e.g. Planke 1994;Nelson et al, 2009). A full sequence of wireline data was available from the Delta-1 well, and this provided an assessment of the type and style of volcanism present in the well.…”
Section: Physical Volcanology Of the Volcanic Successionmentioning
confidence: 99%
“…A typical flood basalt lava flow is divided into three parts (e.g. Self et al, 1997;Nelson et al, 2009): a vesicular/fractured rubbly crust, a massive mostly non-vesicular core and a thin vesicular base. These three parts have very different physical properties: the core has a high density and high V p , whereas the crust has a relatively low density and low V p .…”
Section: Physical Volcanology Of the Volcanic Successionmentioning
confidence: 99%
“…Jerram et al, 2009;Planke et al, 2015;Schofield et al, 2016), as well as an understanding of the petrophysics of the volcanic rocks from borehole core and wireline data (e.g. Planke et al, 1999;Japsen et al, 2004;Nelson et al, 2009;Watton et al, 2014;Millett et al, 2015). With these advances in our understanding of volcanic margins, targeted 3D seismic data over key volcanic areas will provide valuable insights into how these margins develop through time and are preserved in the offshore rock record.…”
Section: Introductionmentioning
confidence: 99%